The influence of the multidimensional Islamic work ethic on employee loyalty: Evidence from KSPPS BMT Yaqawiyyu - Ayuningrum Tri Haryono; Sukmarani Sukmarani; Flora Grace Putrianti (Universitas Ahmad Dahlan, 2026)
This study examined the influence of the Islamic Work Ethic (IWE) on Employee Loyalty among employees of KSPPS BMT Yaqawiyyu from a values-based organizational psychology perspective. Although previous research has consistently demonstrated positive associations between the Islamic Work Ethic and employees' work attitudes and behaviors, the specific contribution of each IWE dimension to employee loyalty remains insufficiently understood. A total of 82 employees of KSPPS BMT Yaqawiyyu participated in this study. Data were collected using the Islamic Work Ethic Scale and the Employee Loyalty Scale and analyzed using multiple linear regression with SPSS version 25. The results revealed that the multidimensional Islamic Work Ethic had a significant simultaneous effect on Employee Loyalty (F = 33.1, p < .001), explaining 56% of the variance in employee loyalty (R² = .560). Partial regression analysis indicated that only the Work as the Manifestation of Aqidah dimension exerted a positive and statistically significant effect on Employee Loyalty (p < .001). In contrast, Work Based on Knowledge (p = .253) and Work by Emulating Divine Attributes and Following Allah's Guidance (p = .262) did not significantly predict Employee Loyalty. These findings support the multidimensional conceptualization of the Islamic Work Ethic and suggest that perceiving work as an act of worship, together with the alignment of employees' spiritual values with organizational values, constitutes a key psychological mechanism underlying employee loyalty in Sharia-based organizations.